2011
DOI: 10.1097/bpo.0b013e31821e10c5
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Vitamin D Deficiency in a Southwestern Luminous Climate

Abstract: A consensus has yet to be established as to what an "optimal" vitamin D level is for growing children to develop strong bones for a lifetime. This study demonstrated that 14% of children living in a sunny climate had vitamin D levels below 20 ng/mL, a level universally accepted as insufficient, and 49% were below 30 ng/mL, arguably a "desired" level. A sunny climate does not assure vitamin D sufficiency. Virtually all children should be supplemented, with laboratory follow-up for those at high risk for low bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 1 publication
1
16
1
Order By: Relevance
“…Wang et al reported that very low birth weight infants had reduced bone mass at ages 5 to 10 years, even after adjustment for height, lean mass, or bone area [47], whereas in the same study, short gestation period was correlated with unfavorable skeletal health among prepubertal boys [47]. Predicated on the concept that vitamin D deficiency [12,13,14,15,16] and BMD [8] are key factors for the development of GPs, further research may reveal if the implication of perinatal risk factors in the bone metabolism process results in the onset of the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al reported that very low birth weight infants had reduced bone mass at ages 5 to 10 years, even after adjustment for height, lean mass, or bone area [47], whereas in the same study, short gestation period was correlated with unfavorable skeletal health among prepubertal boys [47]. Predicated on the concept that vitamin D deficiency [12,13,14,15,16] and BMD [8] are key factors for the development of GPs, further research may reveal if the implication of perinatal risk factors in the bone metabolism process results in the onset of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…However, as there is no reliable and valid assessment tool testing hypermobility in children, the last hypothesis remains unproven [2]. Currently, many studies focus on the correlation of growing pains with bone density [8] and with factors affecting paediatric bone metabolism regarding serum levels of vitamin D or calcium [8] and omega-3 fatty acid intake [12,13,14,15,16]. The bone strength theory, which is closely related to the non-inflammatory pain syndrome theory, is based on the observation that the tibial bone density in children with GPs, as it was measured by quantitative ultrasound, was significantly reduced compared to healthy children [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Other possibilities have been summarised by Evans and Scutter. 7 Adult arthritis has long been considered to be a condition that could be ameliorated or prevented by dietary manipulation, with suggestions of different components of the diet being important-particularly ω-3 fatty acids.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Furthermore, a twin family survey [10] provided evidence that GPs appear genetic susceptibility and present genetic association with Restless Leg Syndrome. Currently, many studies focus on the correlation of Growing pains with bone density [7] and with factors affecting paediatric bone metabolism regarding serum levels of vitamin D, or calcium [7] and ω-3 fatty acids intake [11][12][13][14][15]. The bone strength theory is based on the observation that the tibial bone density in children with GPs, as it was measured by quantitive ultrasound, was significantly reduced compared to healthy children [7].…”
mentioning
confidence: 99%